PENGARUH PENGETAHUAN PERPAJAKAN, PELAYANAN APARAT PAJAK, DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK UMKM YANG MEMILIKI NPWP (Studi Kasus UMKM di Kecamatan Semarang Selatan, Semarang Barat, dan Ngaliyan) - Rudiansyah, 14.05.52.0092; Widiatmoko, Jacobus (Students' Journal of Accounting and Banking, 2018)
This study aims to empirically examine the effect of taxpayer knowledge, theservice of tax officials and tax sanctions on MSME taxpayer compliance. The population in this study were MSME Taxpayers in Semarang City as many as 99 MSMEs in 3 Sub-districts namely, South Semarang District, West Semarang District, and Ngaliyan District. The method used is Judgment Sampling. Where is the method of selecting a sample based on certain considerations, as well as determining the number of samples using the Slovinformula. Test equipment in this study uses Validity Test, Reliability Test, Classic Assumption, and Multiple Linear Regression Analysis Test. The results of this study are the service of the tax authorities does not affect the compliance of MSME taxpayers. Taxpayer knowledge and tax sanctions affect the mandatory compliance of MSMEs. Keywords: Taxation Knowledge, Tax Apparatus Service, Tax Sanctions, UMKM Taxpayer Compliance